FEATURES OF APPLICATION OF THE CONTROL-DIAGNOSTIC APPARATUS FOR TECHNICAL SERVICE OF WATER TRANSPORT VEHICLES - Трофименко, А. О.; Давидов, В. С.; Завітаєв, В. Л. (Science-based technologies, 2019)
The perspective direction of development of water transport vehicles in cargo transportation is shown. The results of the analysis of the technical condition of domestic means of water transport are presented. The role of control and diagnostic equipment in the determined technical state of means of water transport is substantiated. It is shown that the feature is the need to consider the fact of detecting the object of control failure in the investigation of the effectiveness of the system of monitoring the technical state of water transport vehicles. At the same time they do not consider working at this moment. The urgency of the decision of an important scientific and technical task is grounded - development of the method of synthesis of control and diagnostic equipment for the maintenance of water transport means of evaluation. The solution of this problem will allow, with the limitations on material resources, to timely and qualitatively control the technical state of the constituent units (elements) of water transport vehicles. The advantages and disadvantages of control-diagnostic equipment are determined on the basis of control and measuring systems. It is shown that internal means of increasing metrological characteristics of control and diagnostic equipment are calibration and self-report. The promising devices of automated control and diagnostics are intended for checking of workability (capacity), search of places of refusal and performance of works on maintenance of means of water transport or components of complex complexes. The advantages of perspective control-diagnostic equipment are compared with existing means.